Effects of sex and remifentanil dose on rats' acquisition of responding for a remifentanil-conditioned reinforcer. Issue 2 (April 2016) - Bertz, Jeremiah W.; Jackson, Emily L.; Barron, Davina R.; Woods, James H.
Abstract : Opioid-conditioned reinforcement is thought to exacerbate opioid abuse and dependence. Sex/gender can influence opioid abuse behaviors, but the effects of sex/gender on opioid-conditioned reinforcement, specifically, are unclear. In this study, we compared new-response acquisition with opioid-conditioned reinforcement in male and female rats. First, separate groups received response-independent remifentanil injections (0.0–32.0 μg/kg, intravenous) and presentations of a light–noise stimulus. In the experimental groups, injections and stimulus presentations always co-occurred [paired Pavlovian conditioning (PAV)]; in the control groups, the two occurred independently of each other (random PAV). Next, in the instrumental acquisition (ACQ) sessions, two novel nose-poke manipulanda were introduced. All animals (regardless of sex, dose, and PAV type) could respond in the active nose-poke, which produced the stimulus alone, or in the inactive nose-poke. Both males and females dose-dependently acquired nose-poke responding (active>inactive) after paired PAV, but not after random PAV. Therefore, the stimulus was a conditioned reinforcer. We identified three sex differences. First, only females acquired responding after paired PAV with 32.0 μg/kg remifentanil. Second, using a progressive ratio schedule for ACQ, both sexes acquired responding, but females made significantly more active responses. Third, when a single session of PAV was conducted, only males acquired responding. Thus, rats' sex interacts with pharmacological and environmental factors to determine opioid-conditioned reinforcement.